Traqueostomia pediátrica: características de um serviço de assistência em Minas Gerais. - Ligia Maria Alves dos Santos Pertence (2020)
Introduction: Pediatric tracheostomy is an age-old surgery that has undergone important changes in its indications over the last decades, it is currently more indicated in severe and complex patients. Although chronically tracheostomized children are a growing public, the literature about chronic patients is scarce and most studies describe complications with a surgical approach. This study aims to study the prevalence and risk factors for complications in children and adolescents with tracheostomy.Objective: To review the prevalence and factors associated with clinical complications of tracheostomies in children and adolescents. Methodology: A historical cohort study was carried out through the retrospective review of data from the Comprehensive Service for Assistance to Tracheostomized Children (SAIT) of Hospital João Paulo II, Minas Gerais, in the period between March 2011 and July 2017. The final sample consisted of 250 patients with a total evaluation period of five years. Survival and Cox regression Analyses were performed to evaluate proportional risks. This dissertation also has a review article, in which articles were selected from the database of database articles were selected from Cochrane, Latin American and Caribbean Health Sciencies Literature, National Library of Medicine via PubMed and Embase. Articles published between January 2009 and November 2019, which cover the age group between 0 - 18 years old, were included. Results: The overall clinical complication rate in the study was 70% and 50% per year of follow-up, with the most prevalent clinical complication in all years of follow-up being tracheitis, followed by skin injury, accidental decannulation and obstruction. The most common indication for tracheostomy was upper airway obstruction followed by neurological disorders of 52% and 38%, respectively. The main cause of indication for upper airway obstruction was failure of extubation due to obstruction with posterior bronchoscopic diagnosis of glottic or subglottic stenosis (63%). There was a reduction in complications (p =0.005) after entering a specialized service. The main risk factors for tracheitis were comorbidities (RR 1.6; CI: 95%: 1.09-2.69), for decannulation the presence of a plastic cannula without cuff compared to those with cuf (RR, 3.0; CI 95% 1.32-7.12) and for granuloma (RR 4.1, CI 95% 1.38-12, 25) the time between the procedure and admission to the specialized service was a protective factor (0,34, CI 95% 0.12 - 0.94) for granuloma using a plastic cannula with a cuff compared to those without a cuf. In the literature, a general prevalence of complications was found from 4 to 88%. In addition to the temporal definition, the rate of complications also varied due to the severity of operational description. The most frequently described clinical complication was granuloma, which had a prevalence from 0% to 88%. Regarding the obstruction of the cannula or tracheostomy tube, its rate varied between 0% to 57%, whereas accidental decannulation showed a rate from 0% to 27.5%. Bleeding was from 0% to 50%, tracheitis was from 0% to 90%. In relation to aspiration of gastric content, this complication was reported in only three articles with a rate ranging from 0% to 9%. Skin lesions showed rates between 0% and 31%. There was no report of myiasis in pediatric tracheostomy. Another clinical complication not reported was complications involving ballonets or cuffs. Conclusions: This study confirms that the prevalence of clinical complications was high and showed great variability. However, it presented a tendency to reduce and stabilize the rates of the same complications over time. The different operational definitions interfered in the analysis of rates and should be standardized, as they may have implications for the planning of care and costs of assistance to a growing public. In the literature, there is also a high prevalence of clinical complications, with reduction after entry into specialized service, and maintenance over the years. Potentially modifiable risk factors were found, including delay in referral to a specialized service and the type of cannula used. All managerial efforts should be made to make more biocompatible cannulas available and encourage the attachment of these patients to teams trained to assist the tracheostomy patient.